2022
DOI: 10.53730/ijhs.v6n1.3870
|View full text |Cite
|
Sign up to set email alerts
|

Modern learning models through teacher and student dynamic interaction in HEI towards COVID-19 pandemic condition

Abstract: The aims of the study is an empirical assessing the dynamic interaction of a teacher and a student at the HEI during a pandemic as an important component of the distance learning model, identifying methods and ways to ensure the integration of this component in the distance learning program for further use in the practice of HEIs. The methodology is based on the method of case analysis of the University of Oxford in the organization of educational activities during the pandemic following the Business Continuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There was used data from the British Household Panel Survey (BHPS) 1991-1998 to analyzed the impact of changes in income on the health of male and female residents of the UK. The results showed that changes in income had a weak positive effect on the health levels of male residents in both studies using balanced and unbalanced panel data, while changes in income were not associated with the health levels of female residents when using unbalanced panel data (Arunrat et al, 2021;Kiani et al, 2021;Nina et al, 2022). The health-enhancing effect of increased income was only found in the male group and not in the female group.…”
Section: Literature Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…There was used data from the British Household Panel Survey (BHPS) 1991-1998 to analyzed the impact of changes in income on the health of male and female residents of the UK. The results showed that changes in income had a weak positive effect on the health levels of male residents in both studies using balanced and unbalanced panel data, while changes in income were not associated with the health levels of female residents when using unbalanced panel data (Arunrat et al, 2021;Kiani et al, 2021;Nina et al, 2022). The health-enhancing effect of increased income was only found in the male group and not in the female group.…”
Section: Literature Reviewmentioning
confidence: 87%
“…The health-enhancing effect of increased income was only found in the male group and not in the female group. Some scholars were also comparing the health effects of income in urban areas and rural areas (Albert, 2022;Cedeño et al, n.d.;Nina et al, 2022). Fang Ya & Zhou Tripod (2021, found that the health effect of income was more pronounced among urban residents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Early systems that used “clickers” (Katz et al , 2017) have given way to more sophisticated software enabling large cohorts of students to interact during teaching sessions in real-time. Software such as MentiMeter and Vevox enable students to respond anonymously via internet-connected devices using a range of formats such as multiple-choice questions, word-cloud creation or open-text (Vallely and Gibson, 2018; Moorhouse and Kohnke, 2020; Nina et al , 2022). Research into SRS has documented the positive effects of using them in teaching settings, evidencing how they can reduce mind-wandering (Iwamoto and Hargis, 2018) and promote engagement and learning (Blood and Neel, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Science process skills and creativity in science learning are needed to determine the pure competencies possessed by students regarding science learning contents. Those skills and creativity can be generated by the teacher through the provision of appropriate teaching materials and assignments to students (Nina et al, 2022). However, the facts in the reality during COVID-19 pandemic show that not all science assignments and materials gave by the teacher are appropriate and able to improve students' science process skills and creativity (Zydney & Warner, 2016;Gelman & Brenneman, 2004).…”
Section: Introductionmentioning
confidence: 99%